Cross-national competition analysis of China's new energy vehicle supply chain in the post-epidemic era: Take BYD as an example - Niu, Pengbo (International Journal of Global Economics and Management, 2023)
Now that the global epidemic has gradually come to an end, China's new energy vehicles, which have been driven from policy driven to market driven, show a substantial growth trend under the circumstances of the economic slowdown. In domestic tram giant BYD, for example, the analysis of BYD's new energy vehicles on the present situation of the supply chain, put forward the new energy automobile supply chain development and change direction of Suggestions and measures, through SWOT analysis BYD in transnational competition advantages, disadvantages, opportunities and threats, in order to enhance the industrial supply chain independent control ability.